Recent advancements in impedance of fouling resistance and particulate depositions in heat exchangers. (October 2019) - Awais, Muhammad; Bhuiyan, Arafat A.
Highlights: Higher fluid flow rate or flow velocity mitigates fouling resistance and particulate deposition. Impurities accumulate in the region of low velocities. Higher foulant material concentration induce higher fouling rate. Physical water treatment methods impart prominent role in fouling retardation. Fouling rate and particles deposition depicts significant dependency on material surfaces. Abstract: Mitigation of fouling and particulate deposition in heat exchangers is the foremost concern of this critical review study. Formation of vindictive scale, sludge and fouling layers on heat transfer surfaces have severe influence on thermo-hydraulic performance and overall efficiency of heat exchangers. Fouling on gas or liquid side prevent heat transfer from bulk fluid to the solid surfaces resulting lower thermal performance of heat exchangers. Furthermore, fouling layers on heat transfer surfaces induce blockage to the fluid flow and hence increase pumping power by amplifying pressure drop. The use of various system operating variables in controlling fouling and particulate deposition is comprehensively discussed. The influence of flow rate or velocity, temperature, concentration, material surfaces and other miscellaneous factors on reduction of fouling and particle deposition is extensively investigated. It was concluded that higher flow velocity induces strong shear force across heat transfer surface which in results eradicate deposits and reduces the fouling resistance at the expense of higher pressure drop. The enhancement in fouling concentration leads to the higher fouling resistance and materials with lower thermal conductivity yield inferior fouling resistance. To conclude, this review study will be exceedingly useful for designers to design heat exchangers with higher overall efficiency under the influence of fouling.